2019
DOI: 10.1021/acsomega.8b03116
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insights into the Interactions of Two Emerging Bromophenolic DBPs with Human Serum Albumin by Multispectroscopy and Molecular Docking

Abstract: Disinfection byproducts (DBPs) are of high concern due to their ubiquitous existence in disinfected drinking water and their potential adverse effects on human health. In this study, two bromophenolic DBPs 4-bromophenol (4-BrPh) and 2,4-dibromophenol (2,4-DiBrPh) were selected to investigate their binding interactions with human serum albumin (HSA) using spectroscopic techniques and a molecular docking method. The experimental results demonstrated that both of the DBPs could bind with HSA to form bromophenol–H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Human serum albumin (HSA), the most abundant protein in plasma, is quite versatile in function, and plays a role in maintaining the acid–base balance, regulating osmotic pressure, and catalyzing metabolic reactions [ 7 , 8 ]. In addition, HSA is the primary depot and is involved in the transport of exogenous small molecules throughout the body [ 9 , 10 ], which is, consequently, accompanied by conformational changes in its secondary and tertiary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Human serum albumin (HSA), the most abundant protein in plasma, is quite versatile in function, and plays a role in maintaining the acid–base balance, regulating osmotic pressure, and catalyzing metabolic reactions [ 7 , 8 ]. In addition, HSA is the primary depot and is involved in the transport of exogenous small molecules throughout the body [ 9 , 10 ], which is, consequently, accompanied by conformational changes in its secondary and tertiary structures.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence in toxicological and epidemiological research in cell cultures that haloacetonitriles (HANs), e.g., dibromoacetonitrile (DBAN) and 2,3-dibromopropionitrile (DBPN), can invoke adverse effects on the endocrine system by binding to the human estrogen receptor and androgen receptor [50,67]. Additionally, Nakamura et al [68] reported that halogenated derivatives of E1, E2, E3, and EE2 showed estrogenic activity, interfering with estrogen receptor α, using yeast two-hybrid assays between human and medaka fish (Oryzias latipes), The androgen hormone regulates the androgen signaling pathway via binding with the androgen receptor (AR), and it plays an essential role in the physiological processes of human development and reproduction [92]. Iodoacetic acid (IAA) was observed to show AR binding in vitro [50].…”
Section: Hormone Receptor-mediated Mechanism Of Endocrine Disruptionmentioning
confidence: 99%
“…As information about the crystal structures of MCs-PP1/PP2A is limited, it is difficult to elucidate the molecular mechanism for the discrepant inhibition of MCs on PP1/PP2A. Homology modeling could evaluate the interactions between structural analogues and macromolecules, and it has been successively used to evaluate the interactions between drugs/contaminants and proteins [19][20][21].…”
Section: Introductionmentioning
confidence: 99%